Penekanan Sumber Inokulum Rigidoporus microporus dengan Solarisasi Tanah dan Penambahan Bahan Organik - Fitriani, Lisa Bela; Widodo, Widodo (Jurnal Fitopatologi Indonesia, 2022)
Suppression of Rigidoporus microporus Inoculum Sources with Soil Solarization and Organic Matter Amendmend White root rot fungus (Rigidoporus microporus) is one of the devastating plant pathogens on hevea rubber plantation. Its high ability to live as saprophytes on plant stumps and dead roots debris makes this part as an important source of inoculum, both for neighboring healthy trees and at the time of replanting. Therefore, reducing this source of inoculum is an important key to preventing further pathogen dispersal. Soil solarization is a one of the methods of soil disinfection before planting for controlling certain pests and diseases and for reducing the use of synthetic compound in the soil. This study aims to determine the effect of soil solarization and organic matter amendment on the survival of R. microporus. Soil solarization significantly suppressed the survival of R. microporus at both soil depths, 5 and 15 cm from soil surface. Meanwhile, organic matter treatment had no significant effect in suppressing the development of R. microporus. The suppression of the inoculum was higher with longer period of soil solarization. Our results indicate that soil solarization stimulates fluorescent bacteria that may in turn suppress the white root rot fungus.